Investigating hydraulic loads on a crossbar block ramp using two different computational fluid dynamics models and a physical validation model - Helmer, Philipp; Gisen, David; Weichert, Roman (Journal of Coastal and Hydraulic Structures, 2023)
Crossbar block ramps provide bed stability and facilitate ecological connectivity in rivers. Two major sources of uncertainty in determining their design loads are their massively turbulent flow and backwater influence. Here, they were addressed using two computational fluid dynamics (CFD) models (created with OpenFOAM) of a complete crossbar block ramp by recording loads (forces and moments) on single crossbars. To model turbulence, the first model used the Reynolds-averaged Navier-Stokes (RANS) approach, and the second model used Large Eddy Simulation (LES). The flow in both models was transient and the free surface was tracked. Their mesh was identical and consisted of about 30.3 million cells distributed on 480 processor cores. The computed sampling interval was 180 s. The CFD models were tested against measurements of water level and pressure from a physical model. All models were in the same scale, 1: 20/3. Three discharges representing three typical flow regimes were studied in each model. Characteristics of the flow regimes were reproduced in all models. The RANS model was up to 5.3 times faster, but produced excessive waves, which likely caused over- and underestimation of crossbar loads. The LES model showed good agreement to the physical model and could be used for load predictions. However, a longer sampling interval as well as a larger variety of discharges would be required to obtain stochastically reliable estimations for the maximum loads. Both models indicated that unsteady waves in the wake-interference flow regime must be considered to find critical loads. The results can support decisions on the methods for future investigations of hydraulic loads on crossbar block ramps.